Breeding for Efficient Phytate-phosphorus Utilization by Poultry - Diarra, S.S.; Usman, B.A.; Igwebuike, J.U.; Yisa, A.G. (International Journal of Poultry Science, 2010)
The ban of meat meal in poultry feed in most countries of the world and the high cost of fish meal have resulted in the increased use of plant products in poultry diets. However, phytate, which is the main storage form of phosphorus in plants, exerts antinutritional effects in poultry due to its ability to form insoluble complexes with essential minerals and proteins. In addition to these effects, the excretion of excess phosphorus into the environment is a serious cause of environmental pollution. Deactivation techniques such as boiling, fermentation, soaking and enzyme treatment have been used to reduce the level of phytate in plant materials. However, these techniques add to the cost and reduce the nutritional quality of the finished feed through the loss of nutrients. The modes of action of phytate in poultry, its distribution in plants, some common deactivation techniques and their limitations and certain intrinsic qualities of plants that can minimize the effects of phytate in the consuming animal are reviewed. The use of plant and animal breeding as an alternative to deactivation by physical and chemical methods and the use of enzymes are also highlighted.